2004
DOI: 10.1379/csc-1r.1
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock treatment protects against angiotensin II–induced hypertension and inflammation in aorta

Abstract: Angiotensin II (Ang II) is a potent vasoconstrictor and induces inflammation and end-organ injury through its activation of the proinflammatory transcription factor, nuclear factor-B (NF-B). Heat shock (HS) treatment with subsequent expression of heat shock proteins (Hsps) is an effective strategy for tissue protection against oxidative injuries. Recently, HS and Hsps have been shown to interact with NF-B in tissue injury. In this study, we investigated whether HS could protect against Ang II-induced hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…HS has been shown to inhibit ANG II-induced hypertension and inflammation in the heart and aorta (23,34). This suggests the presence of cross talk between HS and RAS.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…HS has been shown to inhibit ANG II-induced hypertension and inflammation in the heart and aorta (23,34). This suggests the presence of cross talk between HS and RAS.…”
Section: Discussionmentioning
confidence: 96%
“…We and others (1,4) have reported that the activation of ANG II is responsible for endothelial dysfunction in insulin resistance. Earlier, HS has been shown to suppress ANG II-induced hypertension and inflammation, but there are no reports suggesting a beneficial role of HS on the ANG-(1-7) pathway of RAS (23). Therefore, we determined vasodilator responses to ANG-(1-7) in insulin resistance condition.…”
Section: Hs Treatment Improves Ang-(1-7)-induced Vasodilator Responsesmentioning
confidence: 98%
See 3 more Smart Citations